Interaction between Air Bubbles and Superhydrophobic Surfaces in Aqueous Solutions - Shi, Chen (Langmuir : the ACS journal of surfaces and colloids, 2015)
Superhydrophobic surfaces are usually characterized by a high apparent contact angle of water drops in air. Here we analyze the inverse situation: Rather than focusing on water repellency in air, we measure the attractive interaction of air bubbles and superhydrophobic surfaces in water. Forces were measured between microbubbles with radii R of 40-90 μm attached to an atomic force microscope cantilever and submerged superhydrophobic surfaces. In addition, forces between macroscopic bubbles (R = 1.2 mm) at the end of capillaries and superhydrophobic surfaces were measured. As superhydrophobic surfaces we applied soot-templated surfaces, nanofilament surfaces, micropillar arrays with flat top faces, and decorated micropillars. Depending on the specific structure of the superhydrophobic surfaces and the presence and amount of entrapped air, different interactions were observed. Soot-templated surfaces in the Cassie state showed superaerophilic behavior: Once the electrostatic double-layer force and a hydrodynamic repulsion were overcome, bubbles jumped onto the surface and fully merged with the entrapped air. On nanofilaments and micropillar arrays we observed in addition the formation of sessile bubbles with finite contact angles below 90° or the attachment of bubbles, which retained their spherical shape